Mapping gene expression in two Xenopus species: evolutionary constraints and developmental flexibility - Yanai, Itai (2011)
Changes in gene expression are thought to be important for morphological evolution, though little is known about the nature or magnitude of the differences. Here we examine Xenopus laevis and Xenopus tropicalis, two amphibians with very similar development, and ask how their transcriptomes compare. Despite separation for ~30–90 million years there is strong conservation in gene expression in the vast majority of the expressed orthologs. Significant changes occur in the level of gene expression but changes in the timing of expression (heterochrony) were much less common. Differences in level were concentrated in the earliest embryonic stages. Changes in timing were prominently found in pathways that respond to selective features of the environment. We propose that different evolutionary rates across developmental stages may be explained by the stabilization of cell fate determination in the later stages.